A case report of vascular hamartoma in a rose-ringed parakeet (Psittacula krameri) - Kheirandish, Reza; Shafiei , Hemad; Soltaninejad , Hamzeh; Hajipour, Pouneh (Journal of Poultry Sciences and Avian Diseases, 2024)
Vascular hamartomas, though rare, can manifest in avian species, presenting diagnostic intricacies for clinicians. A 12-year-old male rose-ringed parakeet presented with a mass between the upper and lower mandibular angles on the left side. The mass was surgically removed. Histopathological examination confirmed the diagnosis of a cutaneous vascular hamartoma. The bird recovered uneventfully and 6 months later showed no evidence of recurrence. This report contributes to the understanding of vascular tumors in avian species.